2010
DOI: 10.1002/pros.21202
|View full text |Cite
|
Sign up to set email alerts
|

Role of monocyte‐lineage cells in prostate cancer cell invasion and tissue factor expression

Abstract: This study shows that co-culture with monocyte-lineage cells induced prostate cancer cell invasion activity. PC-3 invasion and TF expression was induced in co-culture with U-937 cells and partially inhibited with TF neutralizing antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…It has been found that TF/FVIIa involves in cleaving and activating G-proteincoupled PAR2, which further triggers downstream signaling pathways in cancer cells [22,23]. There are growing evidences that TF and PAR2 are overexpressed in a wide range of tumor types, such as breast, colon, prostate, and hepatocellular cancers, and play crucial roles in promoting cell growth and migration [8,[24][25][26][27]. It has been reported that TF/FVIIa/PAR2 axis induces anti-apoptotic protein Birc 3 and prevents apoptosis and cell death of breast cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that TF/FVIIa involves in cleaving and activating G-proteincoupled PAR2, which further triggers downstream signaling pathways in cancer cells [22,23]. There are growing evidences that TF and PAR2 are overexpressed in a wide range of tumor types, such as breast, colon, prostate, and hepatocellular cancers, and play crucial roles in promoting cell growth and migration [8,[24][25][26][27]. It has been reported that TF/FVIIa/PAR2 axis induces anti-apoptotic protein Birc 3 and prevents apoptosis and cell death of breast cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The density, size, and location of tumor infiltrating macrophages in prostate cancer were reported as powerful predictors of patient outcome (11) and prostate cancer specimens harbor increased positive cells expressing the macrophage specific marker CD68 compared to benign glands (12). More recently, it was demonstrated that expression of macrophage colony-stimulating factor (M-CSF) and its receptor colony-stimulating factor-1 receptor (CSF-1R) are increased in primary tumors of patients exhibiting metastatic disease (13), although other studies have demonstrated variable evidence for TAMs during prostate cancer progression (11-12, 14-15). …”
Section: Introductionmentioning
confidence: 99%
“…The up-regulation of TF is a characteristic of malignant cells, and higher TF expression has been associated with increased angiogenesis, metastasis and a poor prognosis in solid cancers such as pancreatic and ovarian cancer [25][30]. Studies in prostate cancer have also shown that TF expression was significantly higher in prostate cancer cells than benign prostatic epithelium and correlates significantly with Gleason score and stage of disease, the expression of VEGF-A, higher micro-vessel density, bone metastases and poor survival [11], [31]–[33]. These observations support the hypothesis that thromboembolic disease is more than an epiphenomenon in patients with cancer and that the clinical hypercoagulable state may be a surrogate for an aggressive tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%